Mapping nutrient and soil fertility indexes for Durum Wheat in the La Mina region of Algeria - Laribi, Abdelkader; Thelaidjia, Rafida; Dehnoun, Zahida (Journal of the Saudi Society of Agricultural Sciences, 2024)
The growing population coupled with a reduction in available agricultural land per capita necessitates smart management practices to boost production per unit area and enhance overall land productivity, ultimately ensuring food security. Thus, evaluating soil fertility and productivity is crucial for sustainable agriculture. This study aims to assess the chemical fertility status of the soils within the irrigated perimeter of la Mina, a region in Algeria known for Durum Wheat production. Thirty-two soil samples were collected from the study area and subjected to analysis for total N, available P and K, and organic matter (OM) concentration. All the soils were basic (pH 7.63–8.95), had low concentrations of total N (0.04 and 0.19 %), low concentrations of available P (7.36 – 30 mg kg−1), low concentrations of available K (<0.4 Cmol kg−1) and low concentrations of OM (0.67–2.37 % by weight). Using a Nutrient Index classification, the overall classification of the soils of the irrigated perimeter of la Mina were low for N, P, K and OM. In addition, the Soil Fertility Index revealed three levels of fertility with a dominance of fertility level 5 (low). Application of the FertiliCalc software for the evaluation of nutrient requirements of Durum Wheat showed average requirements of 183 kg ha−1 for N, 65.8 kg ha−1 for P and 579 kg ha−1 for K. In light of these findings, appropriate agricultural practices, including the addition of fertilizers, are required to build and maintain the needs of Durum Wheat in the study area.